Uji Efektivitas Beberapa Media Tumbuh Alternatif Limbah Organik dengan Penambahan Tepung Kulit Udang terhadap Pertumbuhan Cendawan Entomopatogen Lecanicillium lecanii - Mubarokah, Annafs Zakiyyah; Afifah, Lutfi; Surjana, Tatang; Kurniati, Anik (Lembaga Penelitian dan Pengabdian Universitas Winaya Mukti, 2024)
Alternative control uses the entomopathogenic fungus Lecanicillium lecanii which is propagated using agro-industrial waste as a substrate for the production of locally available conidia. Propagation of L. lecanii was carried out on media supplemented with shrimp shell flour as additional nutrition. This research aims to provide the best alternative media for the growth of L. lecanii. The research was carried out at the Biological Agents Laboratory (BBPOPT), from March to May 2024. The method used was an experiment with a single factor Completely Randomized Design (CRD). This research consisted of 7 treatments in 4 repetitions: K (Corn Media); A (Sugar Bagasse); B (Tea Dregs); C (Sawdust); D (Sugar Bagasse + Shrimp Shell Flour); E (Tea Dregs + Shrimp Shell Flour); F (Sawdust + Shrimp Shell Flour). The results showed that L. Lecanii has a short incubation period, namely one hsi and alternative organic waste media with the addition of shrimp shell flour is more effectively used in the propagation of the L. lecanii fungus and has a significant effect on colony diameter (8.84 cm) in sawdust + shrimp shell flour. Alternative media with the addition of shrimp shell flour is recommended for the growth of the fungus L. lecanii.